PENGARUH SERTIFIKAT HAK ATAS TANAH SEBAGAI ALAT BUKTI DALAM MENCAPAI KEPASTIAN HUKUM - Muthallib, Abdul (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, dan Ekonomi Islam, 2020)
This article discusses legal certainty as one of the objectives of Law No. 5 of 1960 concerning Agrarian (Undang-Undang Nomor 5 Tahun 1960 tentang Pokok-Pokok Agraria) Principles and the influence of land rights certificates as a strong means of proof of land registration. The provision of guarantees of legal certainty to holders of land rights is accommodated in Law Number 5 of 1960 concerning Agrarian Principles and further regulated in Government Regulation Number 24 of 1997 concerning Land Registration (Peraturan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah). Using a normative legal view, this article refers to regulations on agrarian. The discussion of the article looks at the role of the government in providing opportunities for all citizens to register land with the aim of obtaining legal certainty and minimizing disputes. This article looks at the purpose of issuing certificates in land registration activities so that right-holders can easily prove that they are the right-holders. This is done so that rights holders can obtain legal certainty and legal protection. However, the land rights certificate issued is considered to be still lacking in minimizing disputes and it is assumed that it has not affected the land rights owners to protect their rights.